Experiments for the role of sliding connection in rigid faced GRS walls under transverse relative settlement - Mohan Krishna Kolli; Amit Prashant (Soils and Foundations)
The transverse relative settlement of reinforced fill and fascia induces reinforcement loads additional to service loads in Geosynthetic Reinforced Soil (GRS) Walls. The fascia-reinforcement connections need due attention in such conditions for both strength and serviceability considerations. A sliding connection is an alternative to avoid the buildup of high reinforcement connection loads under the relative settlement. 1-g model tests were carried out in an in-house developed relative settlement simulator tank on full-height panel rigid fascia (RF) GRS walls with two types of conventional connection systems. The sliding connection system was developed and proposed for RF-GRS walls, and its performance was assessed under the relative settlement of fill. In RF-GRS walls with conventional connection systems, the maximum tensile strains increased more than 200 times in bottom reinforcement layers under the relative settlement of 0 to 200 mm compared to the end of the construction. The developed sliding connection systems reduced the stress concentrations at the connection and allowed almost free settlement of the fill relative to the fascia. The maximum reinforcement strains were reduced up to 50 times compared to conventional non-sliding connections under the relative settlement of 0 to 200 mm. Hence, the sliding connection systems are recommended in conditions where the relative settlement of fascia and fill is expected to affect RF-GRS walls’ performance.